Autologous Fat Injection Pharyngoplasty in Adults with Velopharyngeal Insufficiency. (February 2020) - Contrera, Kevin J.; Tierney, William S.; Bryson, Paul C.
Objectives: Understand the utility and technique of injection pharyngoplasty with autologous fat for the treatment of mild to moderate velopharyngeal insufficiency in adults without a history of cleft palate. Methods: Consecutive case series of 11 patients (mean [SD] 41 ± 21 years of age) who underwent injection pharyngoplasty with autologous fat from 2012 to 2018 at a tertiary care center. Patients were followed for a mean of 8.6 ± 8 months with pre versus postoperative evaluations of improvement in rhinophonia, dysphagia, and velopharyngeal closure by nasopharyngoscopy (scored: 0, none; 1, mild; 2, moderate; 3, near-complete; 4, complete). Results: Patient selection and surgical techniques are described. Mean improvements were 2.3 ± 0.86 for rhinophonia, 2.0 ± 0.89 for dysphagia, and 3.0 ± 0.95 for velopharyngeal closure by nasopharyngoscopy. Five (45%) patients underwent subsequent intervention, including four repeat fat injections and three sphincter pharyngoplasties. There were two transient complications–donor site hematoma and subjective nasal obstruction. Conclusions: Although objective assessments are lacking to date, this is among the first reports to demonstrate the effectiveness and safety of injection pharyngoplasty with autologous fat for velopharyngeal insufficiency in a population of adults without a history of cleft. We found, on average, moderate improvement in rhinophonia and dysphagia, and near-complete improvement in velopharyngeal closure by nasopharyngoscopy; however, a portion of patients required subsequent intervention.